Reglas para la operación de la cláusula de terminación unilateral (2020)
Traditional Colombian legal dogma teaches that the fundamental principles of the private contract are the private autonomy of the parties and the enforceability of the contract. However, with respect to the forms of termination of the contract, despite the fact that some sectors of the doctrine do not share the idea that the parties have the possibility of agreeing on a clause that allows an act or declaration of will by one of the parties to terminate the contract early and in its own right; which in the contractual traffic is a common practice. Under this scenario, the main objective of this paper is to establish the requirements for the drafting and exercise of such clauses, in order to contribute to minimize the risks of abuse and violation of the principle of Good Faith. To this end, the review of operating rules in Colombian doctrine was addressed, in order to continue with the study of six unilateral termination clauses agreed upon in contractual practice. From the joint analysis of the information taken from these sources, it was identified that despite the existence of rules developed in the doctrine for the drafting of the clauses, these do not necessarily coincide with the level of creativity and discretion of individuals; for this reason, this work contains general conciliatory rules between those identified in the doctrine and those formulated by the autonomy of the contracting parties.